Pilot and Feasibility Studies - Lancaster, Gillian; Thabane, Lehana
Pilot and Feasibility Studies encompasses all aspects of the design, conduct and reporting of pilot and feasibility studies in biomedicine. The journal publishes research articles that are intended to directly influence future clinical trials or large scale observational studies, as well as protocols, commentaries and methodology articles. The journal also ensures that the results of all well-conducted, peer-reviewed, pilot and feasibility studies are published, regardless of outcome or significance of findings. Pilot and feasibility studies are increasingly conducted prior to a full randomized controlled trial. However, these studies often lack clear objectives, many remain unpublished, and there is confusion over the meanings of the words “pilot” and “feasibility”. Pilot and Feasibility Studies provides a forum for discussion around this key aspect of the scientific process, and seeks to ensure that these studies are published, so as to complete the publication thread for clinical research.